Discovery of the first species of Dryinus Latreille (Hymenoptera: Dryinidae) from Burmese amber - Guglielmino, Adalgisa; Olmi, Massimo; Marletta, Alessandro; Speranza, Stefano (Zootaxa, 2018)
Dryinus maderai sp. nov. (Hymenoptera: Dryinidae) is described from Upper Cretaceous Lower Cenomanian, Burmese amber (Myanmar). It is the first species of Dryinus Latreille found in this amber.